Anthropogenic edges, isolation and the flowering time and fruit set of Anadenanthera peregrina, a cerrado savanna tree - Athayde, Eduardo Anversa [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP] (Springer, 2014)
Fragmentation exposes plants to extreme environmental conditions with implications for species phenology and reproduction. We investigated whether isolation and edge effects influence size, flowering time, fruit set, and seedling establishment of Anadenanthera peregrina var. falcata. We compared trees in the interior (n = 85), and on the edge (n = 74) of a cerrado savanna fragment as well as in a pasture (n = 26) with respect to size, flowering phenology, flower and fruit production, fruit and seed set, predispersal seed predation, and seedling establishment. Trees in the pasture were larger and produced a higher number of flowers and fruits than trees on the edge and interior, yet seed set did not differ across environments. The plant size structure explained the flower and fruit production, and the self-compatibility breeding system caused a similar seed set regardless of the environment. First flowering was later and fruit set higher in the interior. We argue that time of first flower influenced the fruit set of Anadenathera. Edge and isolated trees started to flower earlier as a response to microclimatic conditions-mainly temperature-reducing the fruit set. Predispersal seed predation was lower among pasture trees. Conversely, we found seedlings only on the edge and in the interior of cerrado, suggesting that the pasture was of poor quality habitat for Anadenanthera recruitment. Isolation affected the plant size structure and reproduction of Anadenanthera trees. Studies comparing plant phenology under contrasting environmental conditions may offer clues on how global change may affect plant reproduction in the tropics.
Keywords: Edge effects; Population structure; Scattered trees; Fruit set; Reproductive success